2000
DOI: 10.1023/a:1008930521566
|View full text |Cite
|
Sign up to set email alerts
|

Untitled

Abstract: There is little published information on the measurement of health status or quality of life in acute exacerbations of chronic bronchitis. The measure yourself medical outcome profile (MYMOP), the medical outcomes study 6-item general health survey (MOS-6A), and EuroQoL (EQ-5D) were evaluated in 81 patients with acute exacerbations of Type-1 chronic bronchitis presenting at a single general practice centre in Glasgow. The questionnaires were administered at the first clinic visit and at a second visit within 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
15
0

Year Published

2005
2005
2014
2014

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 75 publications
(18 citation statements)
references
References 9 publications
3
15
0
Order By: Relevance
“…The results for the disease-targeted measures administered in this study were similar to those previously reported [5-8]. The magnitude of score differences between stable and exacerbating patients for the disease-specific measures is substantially greater than for the PROMIS measures.…”
Section: Discussionsupporting
confidence: 88%
See 2 more Smart Citations
“…The results for the disease-targeted measures administered in this study were similar to those previously reported [5-8]. The magnitude of score differences between stable and exacerbating patients for the disease-specific measures is substantially greater than for the PROMIS measures.…”
Section: Discussionsupporting
confidence: 88%
“…Several studies have now confirmed that COPD patients experiencing an exacerbation report significantly poorer HRQOL than stable COPD patients using either generic or disease-targeted measures [5-8]. The results for the disease-targeted measures administered in this study were similar to those previously reported [5-8].…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…Sensitivity to change as measured as standardized response means is comparable to other studies using the MYMOP [6],[14]. Patients in our study reported large effects (SRM > .80) on almost all MYMOP scales, reflecting the high proportion of patients also reporting a subjective improvement of their symptoms.…”
Section: Discussionsupporting
confidence: 85%
“…In 2010, the MYMOP was translated to a valid and change-sensitive Chinese version [10]. Studies evaluating the MYMOP have shown its good content validity [11], feasibility [12], and sensitivity to change [13],[14]. Although MYMOP has been mostly implemented in studies in the field of Complementary and Alternative Medicine (CAM), it is capable of measuring effects from a wide variety of health care interventions and is more sensitive to change than the SF-36 instrument [6].…”
Section: Introductionmentioning
confidence: 99%